UNIT 13.13 Application of the PrimRglo Assay Chemistry to Multiplexed Bead Assays. Issue 1 (1st July 2014) - Fang, Liang; Weis, Anna; Wong, Lawrence Kurniawan; Yeh, David Che‐Cheng; Lai, Richard; Corrie, Simon; Barnard, Ross T.
Abstract: In this unit, we describe a multiplex microsphere quantitative PCR. The system is based on the use of two additional oligonucleotides within a single tube PCR reaction. The first oligonucleotide is modified with a single base pair mismatch and is otherwise equivalent to a universal sequence added to the forward PCR primer. Further, this first extra oligonucleotide is coupled to Luminex microspheres. The second additional oligonucleotide is designed to be complementary to the universal sequence, and is modified with the fluorescent dye Cy3. As the PCR reaction proceeds, the second oligonucleotide is able to bind to the microspheres. Thus, quantitative monitoring of PCR progress takes place. The microsphere‐mediated Cy3‐detection is measured using flow cytometry directly after the PCR reaction. This allows a flow cytometer analysis from up to 150 different spheres and, therefore, multiple genes in one reaction. The multiplex microsphere qPCR is demonstrated using three target genes from Influenza A and Neisseria meningitidis . The multiplex microsphere system will enable a higher degree of multiplexing than is possible with currently available qPCR systems. Curr. Protoc. Cytom . 69:13.13.1‐13.13.10. © 2014 by John Wiley & Sons, Inc.